1990
DOI: 10.1038/bjc.1990.257
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyperthermia in combination with melphalan on drug-sensitive and drug-resistant CHO cells in vitro

Abstract: Summary The effect of temperature on the cytotoxicity of melphalan in a pleiotropic drug-resistant mutant CHO cell line (CHR C5) and in its drug-sensitive parent (Aux BI) was studied in vitro using a clonogenic assay. The cytotoxicity of melphalan was significantly enhanced at elevated but non-lethal temperatures (39-41 'C) and hyperthermia potentiated the effect of melphalan in the lethal temperature range (43-44 'C) in both cell lines. The effect of temperature on membrane permeability to melphalan was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…This led researchers to evaluate the clinical potential of hyperthermia using several temperatures (ranging from 40˚C to 43˚C) (1). Localized hyperthermia enhances the cytotoxic process of several antitumoral drugs and has considerable potential in cancer therapy (38,39). This has been explained by a favourable influence on blood flow, cell membrane permeability and drug uptake (40).…”
Section: Discussionmentioning
confidence: 99%
“…This led researchers to evaluate the clinical potential of hyperthermia using several temperatures (ranging from 40˚C to 43˚C) (1). Localized hyperthermia enhances the cytotoxic process of several antitumoral drugs and has considerable potential in cancer therapy (38,39). This has been explained by a favourable influence on blood flow, cell membrane permeability and drug uptake (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Peng et al reported the approaches of in vitro cell based inhibition assays to predict P‐gp drug interaction at the human brain‐blood barrier (BBB) by using a positron emission topography (PET) imaging method . While these assays can be sensitive and useful tools to obtain information on expression and distribution of the P‐gp protein, lack of specificity, reproducibility, and direct measurement hinders the application in the analysis of samples lining up multiple species or data comparison between laboratories owing to the constraints placed by immunoaffinity reagents or fluorescent dyes . In fact, these approaches are qualitative or semi‐quantitative, not allowing quantitative assessment of the degree of P‐gp‐mediated drug resistance.…”
mentioning
confidence: 99%
“…Re-absorption of the 1979; Millar et al, 1986;Bates & Mackillop, 1990) ILP with mitomycin C also resulted in complete remissions in rats (Marinelli et al, 1991). The technique of isolated liver perfusion has been already extensively and successfully tested in patients by different groups (Aigner et al, 1988;Hafstr6m et al, 1990) without serious (post-) operative complications.…”
Section: Effect Ofmelphalan On Tumour Growthmentioning
confidence: 99%
“…& Mackillop, 1990). In most in vitro studies tumour cell dose limiting suggesting a significant survival was less than 0.1% after 20 min to 1 h exposure with elphalan.…”
Section: Effect Ofmelphalan On Tumour Growthmentioning
confidence: 99%